2012
DOI: 10.7589/0090-3558-48.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Wasting Disease on Reproduction and Fawn Harvest Vulnerability in Wisconsin White-Tailed Deer

Abstract: ABSTRACT:Chronic wasting disease (CWD) is a fatal, transmissible spongiform encephalopathy that affects free-ranging and captive North American cervids. Although the impacts of CWD on cervid survival have been documented, little is known about the disease impacts on reproduction and recruitment. We used genetic methods and harvest data to reconstruct parentage for a cohort of white-tailed deer (Odocoileus virginianus) fawns born in spring 2002 and evaluate the effects of CWD infection on reproduction and fawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…In this study we have demonstrated that a CWD susceptible deer species is able to maintain full term pregnancies throughout the course of disease. Our observations are congruent with those of Blanchong et al [58] in white-tailed deer. We have shown that muntjac are a useful model for studying CWD.…”
Section: Discussionsupporting
confidence: 94%
“…In this study we have demonstrated that a CWD susceptible deer species is able to maintain full term pregnancies throughout the course of disease. Our observations are congruent with those of Blanchong et al [58] in white-tailed deer. We have shown that muntjac are a useful model for studying CWD.…”
Section: Discussionsupporting
confidence: 94%
“…Blanchong et al [52] also determined pre-clinical CWD did not negatively impact female reproduction in Wisconsin white-tailed deer. No difference in pregnancy indicates does participate in the rut regardless of CWD infection-status.…”
Section: Discussionmentioning
confidence: 99%
“…This would surely be compounded by CWD infection, particularly in the later stages of disease. This, in combination with the high nonviable birth rates observed in offspring born to CWDinfected muntjac dams (60%) (1), may result in increased offspring mortality leading to lower annual recruitment rates (99). Yet a portion of offspring born to CWD-infected dams that survive to weaning and reproductive age would enter the population as potential asymptomatic carriers.…”
Section: Discussionmentioning
confidence: 99%